Impulse control disorder related behaviours during long‐term rotigotine treatment: a post hoc analysis. (18th July 2016) - Antonini, A.; Chaudhuri, K. R.; Boroojerdi, B.; Asgharnejad, M.; Bauer, L.; Grieger, F.; Weintraub, D.
Abstract : Background and purpose: Dopamine agonists in Parkinson's disease (PD) are associated with impulse control disorders (ICDs) and other compulsive behaviours (together called ICD behaviours). The frequency of ICD behaviours reported as adverse events (AEs) in long‐term studies of rotigotine transdermal patch in PD was evaluated. Methods: This was a post hoc analysis of six open‐label extension studies up to 6 years in duration. Analyses included patients treated with rotigotine for at least 6 months and administered the modified Minnesota Impulse Disorders Interview. ICD behaviours reported as AEs were identified and categorized. Results: For 786 patients, the mean (±SD) exposure to rotigotine was 49.4 ± 17.6 months. 71 (9.0%) patients reported 106 ICD AEs cumulatively. Occurrence was similar across categories: 2.5% patients reported 'compulsive sexual behaviour', 2.3% 'buying disorder', 2.0% 'compulsive gambling', 1.7% 'compulsive eating' and 1.7% 'punding behaviour'. Examining at 6‐month intervals, the incidence was relatively low during the first 30 months; it was higher over the next 30 months, peaking in the 54–60‐month period. No ICD AEs were serious, and 97% were mild or moderate in intensity. Study discontinuation occurred in seven (9.9%) patients with ICD AEs; these then resolved in five patients. Dose reduction occurred for 23 AEs, with the majority (73.9%) resolving. Conclusions: In this analysis of >750 patients with PD treated with rotigotine, the frequency of ICD behaviour AEs was 9.0%, with a specific incidence timeline observed. Active surveillance as duration of treatment increases may help early identification and management; once ICD behaviours are present rotigotine dose reduction may be considered.